61.4k views
2 votes
Hello could you help me solve this question? (9.11 Solving Logarithmic Equations #14)

Hello could you help me solve this question? (9.11 Solving Logarithmic Equations #14)-example-1
User Seffy
by
6.1k points

1 Answer

7 votes

Answer


x_(1)=(-3+33)/(2)

Step-by-step explanation

Given


2\log_{(1)/(2)}(x+2)=\log_{(1)/(2)}(x+10)

We can use the logarithmic properties to simplify our equation, where:


a\log_bx=\log_bx^a


a^(\log_a(x))=x

Applying this rule to both sides of our problem given:


(1)/(2)^{\operatorname{\log}_{(1)/(2)}(x+2)2}=(1)/(2)^{\operatorname{\log}_{(1)/(2)}(x+10)}
(x+2)^2=(x+10)

Solving the squared expression:


x^2+4x+4=x+10
x^2+4x-x=10-4
x^2+3x=6

Setting the equation to 0:


x^2+3x-6=0

Using a scientific calculator to get the result:


x_1=(-3+√(33))/(2)
x_1=(-3-√(33))/(2)

If we verify the solutions the correct one is the first.

User Alex Pilugin
by
6.0k points